Association between CYP2A13 Polymorphisms and Lung Cancer Risk : A Systematic Review and Meta-Analysis of Case–Control Studies - Voon, Fui Ling; Edmund Sim, Ui Hang (Thieme, 2025)
Objectives: Lung cancer remains a leading cause of cancer-related deaths worldwide, with cigarette smoking as a major risk factor. Genetic variations in the cytochrome P450 family, particularly CYP2A13 polymorphisms, have been suggested to influence lung cancer susceptibility. However, their role remains unclear, particularly in relation to smoking status and regional populations differences. This systematic review and meta-analysis aimed to evaluate the association between CYP2A13 combination and homozygous variants and lung cancer risk, stratified by smoking status and geographic region. Materials and Methods: A comprehensive search of electronic databases (PubMed, ScienceDirect, SCOPUS, and Google Scholar) was conducted up to November 11, 2024, to identify eligible case–control studies on CYP2A13 polymorphisms and lung cancer. Inclusion and exclusion criteria were based on exposure of interest, study design, language, type of publication, and reported outcome. Data from 10 studies (2,853 lung cancer cases and 3,651 controls) were pooled to calculate odds ratios (OR) with 95% confidence intervals (CIs), using a random-effects model. Subgroup analyses were performed by smoking status and geographic region. Publication bias was assessed using Egger’s test and funnel plots. Results: A significant association was observed between CYP2A13 polymorphisms and lung cancer risk in specific populations. In East Asian populations, the homozygous variant was associated with an increased lung cancer risk (pooled OR: 1.37, 95% CI: 1.13–1.66). Among smokers in Europe, the combination variant showed a pooled OR of 1.64 (95% CI: 1.21–2.23). In East Asian smokers, the homozygous variant had a pooled OR of 1.52 (95% CI: 1.17–1.96). No significant publication bias was detected. Conclusion: This meta-analysis suggests that CYP2A13 polymorphisms may contrib- ute to lung cancer susceptibility, with smoking serving as a key modifier. The findings are particularly relevant in East Asian and European populations, but given the heterogeneity between studies and limited sample sizes, further large-scale inves- tigations are necessary. These insights provide a foundation for future research on CYP2A13 as a potential biomarker for lung cancer risk.